İsmail Habib’in Eserlerinde Vezin yahut Aruzu Mehmet Âkif’le Anlatmak - Adıgüzel, Muhammet Sani (International Balkan University, 2023)
It is noteworthy that İsmail Habib Sevük also mentions prosody (aruz) while discussing Mehmet Akif Ersoy in his works. Mehmet Akif and prosody are mentioned in many of İsmail Habib’s works, total number of which is around twenty, such as "Türk Teceddüd Edebiyatı Tarihi" at the foremost, " Edebi Yeniliğimiz II ", " Yeni Edebi Yeniliğimiz I Edebiyat Tarihi", "Yeni Edebi Yeniliğimiz II Edebiyat Antolojisi", "Avrupa Edebiyatı ve Biz", "Edebiyat Bilgileri" and "Dil Davası". This topic is in a separate section in the work called "Edebiyat Bilgileri". In this section, İsmail Habib discusses the prosody from the perspective of Turkish poetry. Regarding the subject, He gives examples from the poems of Yunus Emre, Şeyhî, Nef'î, Şeyh Galib, Tevfik Fikret and Mehmet Âkif. In this work, which also points out the place of the prosody in Turkish and literature education, the greatest importance is attributed to Mehmet Âkif. Mehmet Âkif’s name is mentioned forty-one times in total, most of which are in relation to prosody. Mehmet Akif's work "Shadows", in particular, is almost completely analyzed in terms of prosody, and the "İstiklal Marşı" is also comprehensively examined. In this study, İsmail Habib's perspective on Mehmet Akif's poems in terms of prosody has been analyzed in detail through his works. As a result of the research, based on the examined works of İsmail Habib, it was concluded that Mehmet Âkif is one of the poets who used prosody successfully. İsmail Habip describes this success as “Mehmet Âkif, who made the last evolution in terms of adapting the prosody to the Turkish larynx in the 20th century.”
Explaining Meter or Prosody in İsmail Habib’s Works through Mehmet Âkif